Perlindungan Hukum Tenaga Kerja Terhadap Perusahaan Alih Daya (Outsourcing) Atas Uang Pesangon Karena Usia Pensiun (Studi Putusan No. 36/PDT.Sus-PHI/2022/PN. Mks) (PETITUM, 2026)
This study aims to examine the legal protection of outsourcing workers related to severance pay due to retirement age and examine the legal considerations of the judge in Decision Number 36/PDT.Sus-PHI/2022/PN.MKS. The method used is Descriptive Normative. The results of the study indicate that legal protection for outsourcing workers has weakened after the elimination of Article 167 paragraph (5) in conjunction with Article 184 of the Manpower Law by the Job Creation Law. The main risk of outsourcing is the uncertainty of employment status and the right to severance pay. Law Number 2 of 2004 offers dispute resolution through bipartite, tripartite, and litigation negotiations. The importance of an appropriate legal mechanism to guarantee workers' rights. The judge's decision involving the Employing Company is inappropriate, because the responsibility for layoffs should lie with the outsourcing company. The government and lawmakers need to reconsider the elimination of criminal sanctions in Article 184 of Law Number 13 of 2003 which has been eliminated by the Job Creation Law to ensure employers' compliance with workers' rights.